A personalized learning to promote students' learning on programming (Journal of Educational Sciences, 2024)
Today's secondary school curriculum includes computer science as one of its core disciplines, with an emphasis on the fundamentals of programming. Students who are learning write computer code by following the textbook step-by-step without realizing the connections between concepts. Because of this, a lot of students find it difficult to grasp even the most basic programming ideas, making it difficult for them to develop basic programs and eventually acquire and understand more sophisticated ideas. In light of this, this study suggests a customized learning environment that is built on a variety of sources of unique student data, such as learning challenges, learning preferences, and grade levels. Exam response analysis aids in determining the learning challenges that students encounter. Furthermore, a learning styles questionnaire is employed to adjust the presenting style according to the distinct learning type of every learner. Each student's learning resources are also arranged according to their performance level, which is divided into three categories: high, medium, and low. According to data analysis, students who made use of the tailored learning environment were successful in learning the fundamentals of computer programming. The study included quantitative surveys on student views, engagement, satisfaction, and tailored learning preferences in addition to qualitative test analysis.In order to improve students' abilities and learning outcomes, the research focused on the emotional and psychological components of the individualized approach, involving eighth-grade students from Nazarbayev Intellectual School of Physics and Mathematics in Taraz city.Key words: individual approach, programming skill, personalized learning.